Prioritas Pengembangan Permukiman Berdasarkan Analisis Kesesuaian Lahan Di Kota Ambon - Mohammad Amin Lasaiba (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2023)
The development of sustainable settlements requires land suitability analysis. This study aims to analyze land use based on satellite imagery, land suitability classes and criteria for settlements, as well as limiting factors and development priorities. The methods used include qualitative descriptive analysis for spatial analysis and quantitative descriptive analysis to explain the ranking based on land units. The study utilizes Landsat 8 data, administrative maps, soil types, and rock data. Tools used include a compass, camera, and GPS. Data collection is obtained through surveys, satellite imagery, and relevant documents. Data processing tools include ArcGIS 9.3, Er Mapper 7.0, and Global Mapper 15.0 software. Data is collected through field measurements and analyzed based on ranking and overlay techniques. The study results show that land use classification, including geometric and radiometric correction and maximum likelihood classification, demonstrates good accuracy. The classes and criteria for suitable settlement land are predominantly categorized as highly unsuitable, covering an area of 23,592.48 hectares, while the highly suitable category covers an area of 6,033.39 hectares. Settlement development priorities are categorized as Priority I covering an area of 3,181.34 hectares; Priority II, covering an area of 2,852.05 hectares; and Priority III, covering an area of 8,237.89 hectares. The study reveals the existence of settlement development in problematic areas, covering an area of 204.19 hectares. This phenomenon can be explained by the geographical conditions of Kota Ambon, which is primarily hilly, making it the preferred choice for residents in fulfilling their housing needs. Therefore, local governments need to strictly enforce regional regulations to preserve land and prevent potential impacts.